A novel long intergenic noncoding RNA indispensable for the cleavage of mouse two‐cell embryos. (5th August 2016) - Wang, Jiaqiang; Li, Xin; Wang, Leyun; Li, Jingyu; Zhao, Yanhua; Bou, Gerelchimeg; Li, Yufei; Jiao, Guanyi; Shen, Xinghui; Wei, Renyue; Liu, Shichao; Xie, Bingteng; et al.
Abstract: Endogenous retroviruses (ERVs) are transcriptionally active in cleavage stage embryos, yet their functions are unknown. ERV sequences are present in the majority of long intergenic noncoding RNAs (lincRNAs) in mouse and humans, playing key roles in many cellular processes and diseases. Here, we identify LincGET as a nuclear lincRNA that is GLN‐, MERVL‐, and ERVK‐associated and essential for mouse embryonic development beyond the two‐cell stage. LincGET is expressed in late two‐ to four‐cell mouse embryos. Its depletion leads to developmental arrest at the late G2 phase of the two‐cell stage and to MAPK signaling pathway inhibition. LincGET forms an RNA–protein complex with hnRNP U, FUBP1, and ILF2, promoting the cis‐regulatory activity of long terminal repeats (LTRs) in GLN, MERVL, and ERVK (GLKLTRs), and inhibiting RNA alternative splicing, partially by downregulating hnRNP U, FUBP1, and ILF2 protein levels. Hnrnpu or Ilf2 mRNA injection at the pronuclear stage also decreases the preimplantation developmental rate, and Fubp1 mRNA injection at the pronuclear stage causes a block at the two‐cell stage. Thus, as the first functional ERV‐associated lincRNA, LincGET provides clues for ERV functions in cleavage stage embryonic development. Synopsis: The ERV‐associated lincRNA, LincGET, is essential for mouse embryonic development beyond the two‐cell stage. LincGET forms an RNA‐protein complex with hnRNP U, FUBP1, and ILF2, participating in transcription regulation and exon skipping splicing activities. LincGET is a nuclear lincRNA that is GLN‐, MERVL‐, and ERVK‐associated and is only expressed in two‐ to four‐cell mouse embryos. LincGET depletion leads to developmental arrest at the late G2 phase of the two‐cell stage with MAPK signaling pathway inhibition and aberrant exon skipping splicing activity. LincGET forms an RNA‐protein complex with hnRNP U, FUBP1, and ILF2. Abstract : The ERV‐associated lincRNA, LincGET, is essential for mouse embryonic development beyond the two‐cell stage. LincGET forms an RNA‐protein complex with hnRNP U, FUBP1, and ILF2, participating in transcription regulation and exon skipping splicing activities.